Movimento Xingu Vivo Para Sempre: ações, reivindicações e estratégias - MORGADO, Cauê Vieira (Universidade Federal do Pará, 2014)
This dissertation carries out an analysis on a social movement known as Movimento Xingu Vivo Para Sempre, observed from its actions and social actors that composed it. The methodology used is the case study and as methodology techniques to achieve our goal, we chose the semi-structured interviews and participant observation. The main analytical category are the social movements, which reviewed about the optics of the New Social Movements, from authors such as Gloria Gohn and IIse Scherer - Warren. Furthermore, we use some concepts, such as: networks of social movements and opportunity structure, the latter being developed by Tarrow. The main objective was to provide an analysis of the Movimento Xingu Vivo Para Sempre, from their actions, strategies and claims, having regard to the opportunity structure in which this process occurs. The specific objectives we had: A reflection on the dynamics of the social movement studied from its history, analysis of the movement's composition and its form of organization, analysis of the relationship between the movement and the various social segments affected by Belo Monte HPP; analysis of the relationship between the movement and the different political and state institutions. It became clear in our research that the Movimento Xingu Vivo Para Sempre is a network of social movements that has undergone various transformations, especially the rupture and departure of most member entities of the network in 2009.The historical institutional frailty of the region, which is reflected in the lack of public services, contributes to the legitimacy of the movement as a channel for denunciation and opposition. However, rather than present an alternative development project, the movement operates in a defensive manner against the construction of dams on the basin of the Xingu river and the Amazon as a whole, through another network calIed Aliança dos Rios Pan-amazônicos. We also note that the relationship with the different social groups affected is impaired by the criminalization waged against the movement, as well as the small number of militants that integrate it, since the changes occurred from 2009. Lastly, we analyze that, despite the head-on opposition to the executive, the movement has articulations in other state sectors, especially in the judiciary, with emphasis on the Public Defender's Office of Pará and the Public Prosecution Service.